A qualitative study exploring strategies to improve the inter-professional management of diabetes and periodontitis. Issue 2 (April 2020) - Bissett, Susan M.; Preshaw, Philip M.; Presseau, Justin; Rapley, Tim
Highlights: Diabetes and periodontitis (advanced gum disease) have a bidirectional relationship. Reductions in HbA1c follow effective periodontal therapy of up to 3−4 mmol/mol. Guidance recommends joint management of people with diabetes and periodontitis. Our findings suggest no communication between medical and dental professionals. Signposting a patient was suggested as an alternative to direct communication. Abstract: Aims: To explore inter-professional communication and collaboration in guideline-concordant diabetes and periodontitis care. Methods: Qualitative design using iterations of workshops to identify ways to improve multidisciplinary working attended by staff from medical and dental primary care practices, and people with diabetes (n = 43). Workshops were semi-structured around a topic guide. Recruitment was via the UK Clinical Research Network, and a patient and public involvement group in the North of England. Results: Medical practice participants were unaware of the bidirectional evidence linking diabetes and periodontitis and stated that they had never received a referral from a dental professional in this context. The patient participants with diabetes reported never having been informed about the links between diabetes and periodontitis from either their family physician or dentist. Medical and dental practice participants gave negative accounts of inter-professional communication, with claims of inappropriate requests and defensive or non-responses that stymied future interaction. Indirect communication through the patient was suggested as an alternative to direct communication. Conclusions: Indirect referral, whereby the patient is signposted to a healthcare professional, was suggested by medical and dental professionals as a useful alternative to the traditional (and time consuming) letter or telephone call, particularly in the case of suspected diabetes or periodontitis.